Bis(amidinate) ligands in early lanthanide chemistry – synthesis, structures, and hydroamination catalysis. Issue 6 (3rd January 2017) - Kazeminejad, Neda; Munzel, Denise; Gamer, Michael T.; Roesky, Peter W.
Abstract : Bis(amidinate) ligands attached to rigid dibenzofuran and phenanthrene backbones have been introduced into lanthanide chemistry for the first time. Abstract : Bis(amidinate) ligands attached to rigid dibenzofuran and phenanthrene backbones have been introduced into lanthanide chemistry for the first time. Depending on the ligand and on the lanthanide source, either bi- and tetra-metallic macrocycles or monometallic complexes were obtained. The mono- and bi-metallic systems were compared in terms of their reactivity in the intramolecular hydroamination reaction. Depending on the catalyst used (mono vs. bimetallic) different rate laws were observed.